Act like a lady : questionable advice, ridiculous opinions, and humiliating tales from three undignified women - Knight, Keltie, 1982-; Vanek, Jac; Tobin, Becca, 1986- (Rodale Books, an imprint of Random House, 2020)
"The hosts of the popular podcast and E! show LadyGang offer a relatable, empowering, and hilarious take on being unapologetically yourself (even if that's not always your best self) in a manifesto that redefines womanhood for the twenty-first century lady"--